Spillover of Workplace Incivility on Family Satisfaction of Nurses: Role of Work-to-Family Conflict and Family Support - Razzaq, Atqa Abdur; Bowra, Zulfiqar Ahmad; Khan, Sanam (Annals of Human and Social Sciences, 2023)
This study aims to examine the association between workplace incivility and family satisfaction through the mediating variable of work-family conflict. Family support is used as the moderating variable in the association between workplace incivility and work-family conflict. Data were collected from 420 staff nurses working in the public sector hospitals of Punjab, Pakistan. PLS-SEM was used to test the proposed relationships. Employees who have experienced workplace incivility reported lower levels of family satisfaction through the mediating variable work-to family conflict. Family support moderates the relationship between workplace incivility and work-family conflict in such a way that with the increase in family support, the positive association is weakened. This study contributes to the current knowledge and literature with a more comprehensive picture of the work stressors that lead to non-work negative outcomes in the family domain of employees.